2018
DOI: 10.4314/jae.v22i3.6
|View full text |Cite
|
Sign up to set email alerts
|

Preference for imported and Nigeria rice among rural households in Imo State Nigeria

Abstract: This study examined the preference for imported and Nigeria rice among rural households in Imo State, Nigeria. The specific objectives were to ascertain the level of preference of imported and Nigerian rice, determine the factors influencing household preference of imported and Nigerian rice consumed and to identify the major constraints to the consumption of imported and Nigerian rice in the study area. Multi-stage random sampling technique was used in selecting120 respondents. Primary data were collected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
(4 reference statements)
5
4
1
Order By: Relevance
“…A larger percentage (51.7%) preferred imported rice to local rice (Figure 1). This is consistent with the findings that consumers preferred imported rice to Nigerian rice in Imo State, Nigeria (Onu, 2018). In addition, a lower percentage of consumers that preferred local rice (43.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…A larger percentage (51.7%) preferred imported rice to local rice (Figure 1). This is consistent with the findings that consumers preferred imported rice to Nigerian rice in Imo State, Nigeria (Onu, 2018). In addition, a lower percentage of consumers that preferred local rice (43.…”
Section: Resultssupporting
confidence: 90%
“…Low price of rice is one of the minor factors influencing household preference for local rice among the respondents and this is in agreement with the findings of that consumers prefer and can afford to pay for high quality imported rice in contrast to domestic rice brands which are considered to be of poor quality because they often contain dirt, stones, chaff and large quantity of broken or irregular grains and so lack competitive advantage against the imported rice brand (Abdul et al, 2017). Also, the findings of the study are similar to the findings of that consumers prefer and can afford to pay for high quality imported rice in contrast to domestic rice brands which are considered to be of poor quality because they often contain dirt, stones, chaff and large quantity of broken or irregular grains and so lack competitive advantage against the imported brand ( Abdul et al, 2017;Onu, 2018). Note: Mean importance is calculated with the values of 1 for most important and 7 for least important.…”
Section: Attributes That Consumers Consider When Purchasing Ricesupporting
confidence: 79%
See 1 more Smart Citation
“…In Nigeria, Onu (2018) reported that respondents preferred imported to local rice due to ease of preparation. In Malaysia, Abdul Latiff and Ayob (2017), identified consumers' knowledge, perception and attitude as factors influencing consumers' preference and attributed the situation to limited awareness or knowledge on domestic rice availability, and the quality characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Rice is the most commonly cultivated cereal throughout the world today. The African rice is believed to have originated from the wild rice (O. barthii) about 3500 years ago and was domesticated in the inland delta area of Nigeria from where it spread to other parts of Africa (Onu, 2018). The demand for rice in Nigeria is growing faster than any other major staple food with consumption broadening across all socio-economic classes including the poor.…”
Section: Introductionmentioning
confidence: 99%